The Evaluation of Learning Management System (LMS) Canvas amidst Pandemic: Students' Perspectives - Faradillah Haryani; Budi Poniam (Tarbawi : Jurnal Ilmu Pendidikan, 2021)
Due to the spread of the Covid-19 virus, the Pandemic Era shifted face-to-face learning to online distance learning, which faced many challenges. One of the challenges is the decreasing level of student motivation and interactivity. LMS to organize learning materials, assignments, and other learning activities is an alternative that facilitates the learning process during the pandemic. Through LMS, lecturers can share materials, give assignments, and provide feedback to students through an integrated online system. This research aims to examine the effectiveness of using LMS Canvas at Sampoerna University, especially pedagogic quality during the pandemic. In this study, researchers used a questionnaire adapted from the LMS Evaluation model by Mtebe & Raisamo (2014) by adding pedagogical quality, including teaching quality, interactivity quality, and student understanding quality. The results of the study state that these three components have a positive effect on user satisfaction and the use of LMS.